Influence of fructooligosaccharide on pharmacokinetics of isoflavones in postmenopausal women - Supanimit Teekachunhatean (2018)
The objective of the present paper was to determine the influence of fructooligosaccharide (FOS) on the pharmacokinetics of isoflavones in healthy postmenopausal women. The study was a fixed-sequence, two-phase, crossover study. Twelve subjects received a single oral dose of 300mL of a soy beverage. Blood samples were collected before the dose and at 0.5, 1, 2, 4, 6, 8, 10, 12, 24, and 32h after the administration of the soy beverage. After a washout period of at least 1 week, subjects were assigned to receive oral doses of FOS, 5g each time, twice a day (after breakfast and dinner) for 14 days, followed by a single oral dose of the same soy beverage on the next day. Blood samples were then collected at the same time points mentioned previously. Plasma isoflavone concentrations were determined by HPLC. Continuous oral administrations of FOS followed by a single oral administration of soy beverage caused significant increases in C max, AUC032, and AUC0∞ of genistein and AUC032 of daidzein, comparing to those obtained following a single oral dose of soy beverage alone. Other pharmacokinetic parameters (T max and t 12 of both aglycones and AUC0∞ of daidzein) between both regimens were not significantly different. Copyright © 2012 Supanimit Teekachunhatean et al.